2015
DOI: 10.1186/s12936-015-0819-8
|View full text |Cite
|
Sign up to set email alerts
|

Indoor use of attractive toxic sugar bait (ATSB) to effectively control malaria vectors in Mali, West Africa

Abstract: BackgroundAttractive toxic sugar bait (ATSB) solutions containing any gut toxins can be either sprayed on plants or used in simple bait stations to attract and kill sugar-feeding female and male mosquitoes. This field study in Mali demonstrates the effect of ATSB bait stations inside houses as a vector control method that targets and kills endophilic African malaria vectors.MethodsThe studies were conducted in five villages located near the River Niger, Mali. Baseline village-wide assessments of densities for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
67
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 33 publications
0
67
3
2
Order By: Relevance
“…ATSBs can be used in outdoor bait stations, indoor bait stations, or can be sprayed directly onto non flowering vegetation [3537]. The products appear inexpensive and require minimal change in user behavior [38]. Moreover, the wide choice of candidate stomach toxins creates options for control of mosquitoes resistant to the currently used contact insecticides [39].…”
Section: Candidate Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…ATSBs can be used in outdoor bait stations, indoor bait stations, or can be sprayed directly onto non flowering vegetation [3537]. The products appear inexpensive and require minimal change in user behavior [38]. Moreover, the wide choice of candidate stomach toxins creates options for control of mosquitoes resistant to the currently used contact insecticides [39].…”
Section: Candidate Toolsmentioning
confidence: 99%
“…A similar study in the Rift Valley showed a 95% reduction in female Anopheles sergentii populations, while completely eradicating males [41]. Even with indoor bait stations, both males and female mosquitoes were attracted to and fed from this source, with more than 90% reduction in populations [38]. Moreover, these studies report changes in population age structure towards younger mosquitoes; an important result as it is the old mosquitoes that are responsible for transmission.…”
Section: Candidate Toolsmentioning
confidence: 99%
“…RNAi knockdown in larvae by per os exposure is efficacious using scalable bacterial and yeast expression systems, demonstrating potential for RNAi in larval control applications [13,27]. Novel interventions have also been explored to provide oral applications to adults in the form of Attractive Toxic Sugar Baits (ATSB) [28,29,30,31,32,33,34,35,36,37]. Formulations for ATSBs include simple sucrose solutions and complex mixtures of fruit sugars with minimal effects on non-target organisms [30,36,38].…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly high ATSB efficacy has been found in spray formulations on flowering and non-flowering plants in arid and wet climates [30,31,35,36,39]. Additionally, strategically placed ATSB stations near breeding sites (dubbed Attractive Baited Oviposition Trap, ABOT) or indoors can attract and kill vector species in proximity to people [32,33,40,41]. Although ATSB have not been studied in conjunction with RNAi, successful gene silencing by oral exposure routes has been documented using sucrose meals and artificial blood meals demonstrating the potential in combining these control approaches [11,42].…”
Section: Introductionmentioning
confidence: 99%
“…Most formulations of ATSB involve the use of fruit juices from guavas and mangoes as phytochemical lures, sugar solution as feeding stimulant, and an oral toxin of 1% boric acid that kills mosquitoes upon ingestion [106, 160]. The technique has been successfully deployed for mass trapping of mosquitoes during vector surveillance operations, and for studies aimed at reducing the proportion of endophagic female mosquitoes [163]. Although this new technique is still in the early stages of development, upscaling of its potential to cover large field applications would prove it a powerful malaria vector management tool that complements the existing vector control strategies.…”
Section: Introductionmentioning
confidence: 99%